SEASONAL FLUCTUATIONS OF ZOOPLANKTON IN RENUKA LAKE, HIMACHAL PRADESH - CHAUHAN, RAMESH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
Seasonal distribution of zooplankton in Renuka lake showed highest population density during rainy season in July and lowest during winterin January. The absolute number of copepoda was always higher than cladocera except for a month. Total zooplankton population was found highly significant and positively related to the water temperature, phosphate-phosphorus and chemical oxygen demand.